Looking for High-Mass X-ray Binaries in the Small Magellanic Cloud - Maravelias, G.; Zezas, A.; Antoniou, V.; Hatzidimitriou, D.; Haberl, F. (2013)
The Small Magellanic Cloud (SMC) is host to approximately 100 High-Mass X-ray Binaries (HMXBs), predominantly Be X-ray Binaries (BeXRBs), a number which is surprisingly high when compared to the Milky Way. As these galaxies present different metallicities it is reasonable to ask if their populations of HMXBs are different. In order to address this we investigated their properties such as their spectral types and orbital parameters (periods and eccentricities). We find no apparent differences, implying that the nature of these systems is similar which sets at the same time strong constraints on the magnitude of supernova kicks in low metallicities. In order to extend the sample of BeXRBs we performed a systematic photometric survey of selected active regions of the SMC. Since the optical counterparts of the BeXRBs display Halpha excess they can be identified through Halpha imaging. Observations in 5 regions with the Wide Field Imager at the 2.2m MPG/ESO telescope yield approximately 24000 Halpha emitting stars. By cross-correlating these sources with those identified in the Chandra and XMM-Newton shallow surveys of the SMC and the census of HMXBs of Liu et al. (2005), we find 34 Halpha emitting X-ray sources. These are most likely BeXRBs, which we will confirm with follow-up spectroscopic runs.